1804-1835 KHARKIV UNIVERSITY’S FACULTY OF MORAL-POLITICAL DEPARTMENT. PART I - Пересада, О. О. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2017)
In the current article, the moral and political department of Kharkiv University which was important in the development of political science in Ukraine and the Russian Empire in 1804-1835 is described. Frameworks of the new university structure were determined by the University charter of 1804. In the article was made an attempt to summarize the knowledge about the department of moral and political science from the 1804-1835. The department of moral and political sciences of the University during the period was reviewed, teaching activities of professors and associate professors of the department were also analyzed.